Robust time-frequency synchronization for OFDM mobile applications - Kleider, J.E.; Humphrey, M.E. (ISSPA '99 : proceedings of the Fifth International Symposium on Signal Processing and its Applications, August 22-25, 1999, Brisbane Convention & Exhibition Centre, Queensland, Australia, 1999)
Orthogonal frequency division multiplexing (OFDM) has become a popular multicarrier transmission scheme for transmission of data requiring high data rates. We present a digital synchronization technique that provides accurate timing and frequency tracking estimates for severely degraded and noisy channel environments. In addition, the synchronization technique can correct large timing misalignment of the received OFDM symbols, and provides acquisition of frequency offsets on the order of multiple sub-channel spacings. Algorithm complexity is minimized by deriving timing and frequency error estimates from the same basic algorithm, making it suitable to handheld radios. The estimation accuracy is excellent, even for very low signal-to-noise ratios. The algorithmic converges within one baud interval, and thus provides a good solution for systems requiring rapid acquisition and symbol timing alignment at system startup.